SISTEM PERINGATAN DINI TERHADAP PENCURIAN SEPEDAH MOTOR MENGGUNAKAN MIKROKONTROLER ATMEGA 328 ARDUINO UNO - Permana, Eka; Setiadi, Kendi (Jurnal Teknologi Informasi dan Komunikasi, 2023)
Motorcycle theft is a prevalent issue that often results in significant losses for its owners. In addressing this challenge, this research introduces an Early Warning System for Motorcycle Theft utilizing the ATmega328 microcontroller, particularly the Arduino Uno. The system is designed to detect unusual movements or vibrations in the motorcycle. Vibration and motion sensors are installed on the motorcycle to monitor suspicious activities. The ATmega328 microcontroller acts as the brain of the system, analyzing inputs from the sensors and triggering an alert when potential theft is detected. Early warnings can be implemented through various channels, including the use of alarms, message notifications, or sending information to the owner's device via wireless connectivity. The system's advantage lies in its ability to provide a rapid response to potential theft situations, offering a greater opportunity to prevent losses. Through the utilization of microcontroller technology and sensors, this research contributes to the development of effective and affordable security solutions for safeguarding valuable assets such as motorcycles. The implementation of this system is expected to be a proactive step in enhancing motor vehicle security and providing peace of mind for the owners.